EFEKTIVITAS KOMPRES BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA ANAK DI WILAYAH PUSKESMAS SELOGIRI - Pratiwi, Gita; Ambarwati, Retno; Marni, Marni; Wahyuningsih, Wahyuningsih (Akademi Keperawatan Giri Satria Husada Wonogiri, 2021)
Shallots (Allium Cepa var. ascalonicum) is a multipurpose tuber vegetable, can be used as a cooking spice, vegetable, cooking flavoring, as well as a traditional medicine because of the antiseptic effect of aniline and allicin compounds it contains. The purpose of this study was to determine the effect of giving shallot compresses to decrease body temperature in children. This study uses a case study design using a nursing process approach. The population in this study with a number of 3 people who were selected based on predetermined criteria. The results of this study indicate that there is an effect of giving shallot compresses to decrease body temperature in children. The results of this study are expected to provide new insights and can also increase knowledge about the use of shallot compresses.